FORMULATION AND IN VITRO EVALUATION OF SUBLINGUAL TABLETS OF PIROXICAM - Meghraj Suryawansh; Jailani S
This study focuses on the development and evaluation of sublingual tablets for piroxicam, aiming to enhance its bioavailability and patient compliance. Preformulation studies confirmed the drug$1 (Bs identity and purity through melting point analysis, UV-Vis spectroscopy and FT-IR, while solubility test highlights its low solubility in water and buffer, but higher solubility in ethanol. Formulation strategies incorporated varying microcrystalline cellulose (MCC) to polymer or to super disintegrant ratios to improve blend flow and compressibility. Among the formulations tested, A4, containing 5% Kyron T-314, emerged as the most optimized formulation, showing the best pre-compression and post-compression characteristics. It demonstrated superior hardness, low friability, rapid wetting and disintegration times, and achieved nearly complete drug release within 9 minutes. Stability studies over three months confirmed that formulation A4 maintained its physical and mechanical properties. Hence, this formulation is considered highly effective for achieving rapid drug release and improved stability, addressing the need for quicker onset of action and enhanced patient adherence.s